Mathematical modelling of rice farmers’ exposure to pesticides with endocrine-disrupting properties - Saiful Ikhwan Nor Arifin (2021)
This study investigates rice farmers’ exposure to pesticides with endocrine-disrupting properties by using mathematical modelling for non-dietary routes of exposure via dermal and inhalation. A total of 13 rice farmers were estimated for their exposure to single active substances applied on a daily basis from June to September 2019, using the Agricultural Operator Exposure Model and the WHO Generic Risk Assessment Model for Indoor and Outdoor Space Spraying of Insecticides and to predict pesticide exposures during mixing/loading and application activities. Then, the estimated exposures to applied active substances on a spraying day were assessed against the no observed adverse effect level of endocrine-disrupting properties for the risk level using hazard quotient (HQ) method. In this study, the 13 selected rice farmers applied 4 – 14 pesticide products with a total of 6 – 19 active substances applied across a whole cropping season. Overall, the estimated exposures were influenced by the use of wettable powder formulation during mixing/loading activities, with overestimation of the risks indicates the need to consider the use of PPE in exposure modelling. There were two applications with HQ values larger than 1 (1.7 and 46.4) because of the use of high toxicity active substances, namely deltamethrin and lambda-cyhalothrin. Study findings indicate the mathematical modelling can be used to monitor pesticide uses and exposures in rice fields, with further refinement deems necessary when data become available.